​ The Relationship Between Environmental Factors and Monitor Distance with Computer Vision Syndrome Complaints Among Employees of The East Java Provincial Health Office - Ilham Fadhillah Akbar; Candraning Diyanah, Khuliyah; Sukma Pawitri, Aditya; Jassey, Babucarr (Universitas Nahdlatul Ulama Surabaya, 2024)
The East Java Provincial Health Office employs most office workers who frequently use digital devices like computers to support their work performance. This study is an analytical observational study utilizing a cross-sectional design. A sample of 41 respondents was obtained. The variables investigated include age, gender, room lighting, room temperature, and monitor distance, all about complaints of computer vision syndrome. The study found significant associations between complaints of computer vision syndrome and the following variables: room lighting (p = 0.001), room temperature (p = 0.001), and monitor distance (p = 0.001). There is a significant relationship between environmental factors, specifically room lighting and temperature, as well as monitor distance and the occurrence of computer vision syndrome among office workers.